Membrane fatty acid heterogeneity of leukocyte classes is altered during in vitro cultivation but can be restored with ad-hoc lipid supplementation. Issue 1 (December 2015) - Poggi, Paola; Mirabella, Roberto; Neri, Simona; Assirelli, Elisa; Dolzani, Paolo; Mariani, Erminia; Calder, Philip; Chatgilialoglu, Alexandros
Abstract Background The cell membrane is a primary and fundamental player in most cellular processes, and fatty acids form a major structural component of cell membranes. The aim of this study was to compare the membrane fatty acid profiles of different human blood leukocytes and selected cell lines, to identify the effects of in vitro culture on fatty acid profiles, and to test medium supplements for their effect on fatty acid profiles. Methods Different classes of leukocytes were isolated from human blood and their membrane fatty acid profiles were analysed and compared. After culturing in vitro immortalised and primary leukocytes, membrane fatty acids were analysed and compared. Finally, different lipid formulations were developed and used for supplementing leukocytes in vitro in an effort to maintain the in vivo fatty acid profile. Descriptive and analytical tests were performed to compare the obtained fatty acid profiles. Results Membrane fatty acid profiles of primary human CD4+ T-lymphocytes, CD8+ T-lymphocytes, B-lymphocytes and monocytes differed. Moreover, there were differences among Jurkat, Raji and THP-1 cell lines and the corresponding primary leukocyte classes, as well as between freshly prepared and in vitro cultured primary lymphocytes. A lipid supplement was able to maintain cultured Jurkat cells with a membrane fatty acid profile almost identical to that of the primary CD4+ T-lymphocytes. Finally, variations in the lipid supplement composition enabled the development of Jurkat cells with different membrane fatty acid profiles characterising different physiological or pathological human conditions. Conclusions Each leukocyte class has its own specific membrane fatty acid profile in vivo. Cultured primary leukocytes and immortalized leukocytic cells display different membrane fatty acid profiles when compared to their respective in vivo counterparts. The membrane fatty acid composition of cultured cells can be restored to reflect that of the corresponding in vivo condition through use of optimised lipid supplementation. Typical physiological or pathological leukocyte membrane fatty acid profiles can be obtained by tuning in vitro fatty acid supplementation.